مكافئة الأحمال الكهربائية في شبكات التوزيع الشعاعية - جـبل, فـؤاد (Latakia University Journal -Engineering Sciences Series, 2019)
يهدف البحث بشكل أساسي لتقديم نموذج رياضي يمكننا (تحليلياً) من مكافئة الأحمال الكهربائية الموزعة ضمن شبكات التوزيع الكهربائية الشعاعية والمكونة من أنواع مختلفة من الأحمال التي تكون خصائصها معروفة عند البارات الفرعية التي تربط إليه هذه الأحمال، إضافة إلى تحديد المعاملات المميزة للحمل المكافئ عند بار التغذية الرئيسي لنظام قدرة كهربائي شعاعي آخذين بعين الاعتبار تأثير عناصر النقل (المغذيات والمحولات). يتم تطبيق الطريقة المعروضة ضمن البحث على الأحمال الساكنة، كما يمكن تطبيقها أيضا لإيجاد التغيرات الحاصلة في الاستطاعة الردية والفعلية عند حدوث تغيرات بسيطة وضمن المجال المحدد لكل من التردد والجهد. تم كتابة برنامج على الحاسب الآلي، يمكن من خلاله وبسهولة دراسة أداء شبكات التوزيع الشعاعية. This paper aims at introducing a mathematical model to equate distributed load in radial networks which consist of different types of electric loads connected to individual busbars where characteristics are known. It also tries to determine the characteristic parameters of equivalent load at the main supply busbar of radial power system in relation to individual distributed loads in a power system taking into account the effect of transmission elements (feeders and transformers). The suggested method is applied in the steady state, but it may also be applied to determine the changes in the active and reactive power due to changes within concern limits of power supply voltage and frequency. A computer program was set that can easily be used to study the performance of radial electric networks.